Stereotypes in linguistic innovation: The case of ’en plan’ in European Spanish - Escalona Torres, Juan; DiBartolomeo, Megan (Borealis – An International Journal of Hispanic Linguistics, 2024)
The discourse marker “en plan,” akin to English “like,” has gained attention due to its rapid spread across Spain. Using explicit and implicit attitude surveys, we examine perceptions of quotative marker “en plan” by Spaniards. Our findings show that “en plan” is mainly associated with younger age groups and casual speech, leading to mixed social attitudes. While some view it as a marker of youth speech and sociability, others see it as indicative of a lack of social refinement or education. The study highlights generational divides, with older speakers often stigmatizing its use, while younger speakers show neutral and positive attitudes. These attitudes reflect broader societal views on language, age, and identity. By focusing on the social perceptions and stereotypes associated with “en plan,” this research underscores the complex relationship between language and social identity, offering insights into how linguistic forms represent particular social groups and influence interactions within the speech community.